Variations from SARS-CoV-2 to Omicron: A new threat knocking at World’s door - Acharya Balkrishna, Akansha Rohela, Ashwani Kumar, Vedpriya Arya, Nazam Khan (Journal of Applied Pharmaceutical Science, 2022)
The public health threat posed by SARS-CoV-2 has persisted since December 2019. Many countries were able to manage SARS-CoV-2 due to various strategies like masking, social distancing, and vaccinations. Virus mutations are one of the most significant barriers to the disease's eradication; as a result, various variants have emerged (Alpha, Beta, Gamma, Delta, etc.) from time to time with higher mortality. Omicron, a variant identified from South Africa, has put the world on high alert. In this context, we have reviewed some reports on Omicron along with other variants. This new variant has been designated as a variant of concern by the WHO. The preliminary reports revealed that Omicron is heavily mutated with more than 30 mutations (A67V, del69-70, T95I, del142-144, Y145D, etc.) in its spike protein. Despite vaccination with the most efficacious Pfizer candidate, Omicron infection was reported in South Africa. Bioactive lipids such as arachidonic acid, alpha-linolenic acid, docosahexaenoic acid, eicosapentaenoic acid, and others have been reported to be the key components in inactivating the virus, so their future role is imperative. Ongoing research for the development of new or modification of existing vaccines must continue.
Keywords: Omicron, SARS-CoV-2, Mutations, Variant of concern, Bioactive lipids